CRISPR/Cas9-Mediated Efficient Targeted Mutagenesis in Sesame (Sesamum indicum L.) - You, Jun; Li, Donghua; Yang, Li; Dossou, Senouwa Segla Koffi; Zhou, Rong; Zhang, Yanxin; Wang, Linhai (Frontiers in Plant Science, 2022)
The clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) system has been widely utilized for targeted genome modification in a wide range of species as a powerful genome editing technology, providing significant benefits for gene functional research and molecular breeding. However, to date, there is no research of any genome editing in sesame (Sesamum indicum L.), which is an ancient and important oil crop widely used in food, medicine and industry. Herein, the CRISPR/Cas9 system along with hairy root transformation was used to induce targeted mutagenesis in sesame. Two single guide RNAs (sgRNAs) were designed to target two sesame cytochrome P450 genes, CYP81Q1 and CYP92B14, respectively, which were involved in lignan biosynthesis. Sequencing data illustrated the expected indel mutations at the target sites, with 90.63% and 93.33% mutation frequency in CYP81Q1 and CYP92B14, respectively. The most common editing event was single nucleotide deletion and insertion. Sequencing of potential off-target sites of CYP92B14-sgRNA showed no off-target events in cases of three mismatches. Metabolomics analysis showed that the biosynthesis of lingans (sesamin and sesamolin) was effectively disrupted in the mutated hairy roots, further confirmed the crucial role of CYP81Q1 and CYP92B14 in sesame lignan biosynthesis. These results not only demonstrated that targeted mutagenesis was efficiently created by the CRISPR/Cas9 system, but also confirmed that CRISPR/Cas9 in coupled with hairy root transformation is an effective tool for assessing gene functions in sesame.